Polyclonal VDAC3 antibody decreases human sperm motility: a novel approach to male contraception (Faculty of Medicine Universitas Indonesia, 2011)
Background: Voltage dependent anion channels (VDAC) mediate transport of anions, cations and ATP which play an important role in sperm motility. This study was aimed to examine the effect of polyclonal VDAC3 antiserum to human sperm motility. Methods: Polyclonal VDAC3 antiserum used in this study was produced in rabbits by immunization of VDAC3-specific synthetic peptides. Preimmunserum was collected before immunization and used for control experiment. Recognition of VDAC3 antiserum to antigen in human sperm was performed by western blot. Thirty sperm samples obtained from fertile men which had high quality of sperm motility were washed and collected by Percoll gradient. Sperm motility was assessed by means of evaluation of sperm velocity (seconds per 0.1 mm distance) and the number of unmoved sperm (million per ml) which were observed 0 minute, 30 minutes and 60 minutes after addition of VDAC3 antiserum and preimmunserum as a control. Both data were analyzed by SPSS 13.0 software. Results: VDAC3 antiserum recognized VDAC3 protein in human sperm. Statistical analysis demonstrated that there were increasing numbers of unmoved spermatozoa after addition of anti-VDAC3 antiserum in vitro for 60 minutes observation compared with preimmunserum (control). We found also that sperm velocity decreased signifi cantly after giving anti-VDAC3 antiserum in vitro for 0 minute, 30 minutes, and 60 minutes compared with pre-immunee serum (control). Conclusion: VDAC3 antiserum can decrease motility of human sperm. and may provide a novel principle of male contraception in the future. (Med J Indones 2011; 20:5-10) Keywords: VDAC3 antiserum, sperm, motility, contraception